An analysis of the availability of and access to credit from the formal financial sector and the performance of SMEs - Asah, Francis Tangwo (Rhodes University, Faculty of Commerce, Department of Management, 2019)
As a developing nation, South Africa faces a high rate of poverty, high levels of inequality in terms of income and a high rate of unemployment. It is officially estimated that about 27.2% of the economically active population are unemployed. SMEs are expected to be an important vehicle to address the challenges of job creation, sustainable economic growth, equitable distribution of income and the overall stimulation of economic development. SMEs in South Africa constitute 99% of all businesses, contributing to employment, income inequality and poverty alleviation (Statistic South Africa, 2018). However, despite the remarkable contribution of SMEs to the economy of South Africa, the failure rate of SMEs (at 75%) is the highest of all the efficiency-driven economies sampled by the Global Entrepreneurship Monitor (GEM). The World Bank affirm that the availability of and access to credit from the formal financial sector is the primary cause of the high failure rate of SMEs. Contemporary literature advance that the future survival and performance of SMEs in South Africa is pegged onto the amount of financial capital available to address their capital needs. Thus, this study sought to analyse the availability of and access to credit from the formal financial sector and the performance of SMEs from the supply and demand-side. In order to achieve the objectives of the study, a sequential exploratory mixed method research design, located in the pragmatic research paradigm, was used in a two phased approach. The qualitative data collection and analysis in Phase 1 informed the quantitative data collection and analysis Phase 2. In Phase 1, in-depth face-to-face semi-structured interviews were conducted with 8 credit and 8 business managers representing the sampling unit of selected formal financial institutions. The qualitative data collected was analysed using the five-steps process of content analysis as illustrated by Terre Blanche et al. (2006:322-326). The main findings with regard to factors that impact on the willingness of the formal financial sector to provide credit to SMEs were collateral, annual business turnover, audited financial records, relationship with the bank, credit profile, nature of the business, economic climate, ethics, nationality, government policy, management team, valid Identity Document/permit, equity contribution, entrepreneurship education, product quality, and business intelligence. Assessing credit applications from SMEs, risk assessment, inspection of financial records, proper documentation and background checks were the different tasks performed by credit and business managers. In addition, the main challenges faced by the formal financial sector in assessing and approving credit in favour of SMEs included the following: lack of investment capital; lack of collateral; lack of proper financial records; poor managerial knowledge; poor business plan; lack of industrial knowledge; and poor legal and credit laws. Lastly, contrary to the notion that formal financial institutions are not interested in investing in SMEs, on average, 70% of SMEs that applied for credit received such credit. In Phase 2, a self-administered questionnaire was used to collect data from formal sector owner/managers of SMEs in the city of Johannesburg. Of the 702 questionnaires distributed, 300 were returned and useable. Data was analysed using the Statistical Package for the Social Sciences (version 24). A test for normality was performed using Shapiro"“Wilks test. Reliability was tested using the Cronbach's Alpha Coefficient. Exploratory factor analysis tested the validity of factors that prevent formal financial sector from granting credit to SMEs while Binary logistic regression was used to infer on the hypotheses. Spearman's Rho correlation analysis was used to determine whether there was any significant relationship with factors that influence access to credit and SMEs performance. The main findings revealed that access to bank finance was the only challenge that showed a significant correlation with performance. In addition, the study revealed that the South African Identity Document and collateral were the most important factors considered when applying for credit from formal financial institutions. With regard to the reasons why formal financial institutions may refuse to grant credit to SMEs, it was revealed that there was no significant positive relationship between lack of business networking and access to credit from the formal financial sector to SMEs. Conversely, the study also revealed a significant positive relationship between collateral, business information, managerial competency, business intelligence, business ethics, entrepreneurship education, legal system and macro-economy and access to credit from the formal financial sector to SMEs. Thus, it was established that there is a significant positive relationship between access to credit from the formal financial sector and the performance of SMEs.
Keywords: Small business -- South Africa -- Finance; Microfinance -- South Africa; South Africa -- Economic conditions -- 1991-